Efektivitas Brain Based Learning Berbantuan Wordwall terhadap Kemampuan Berpikir Kritis Peserta Didik - Profithasari, Nindy; Lutfiani, Uswatun Isna; Rapani, Rapani (Jurnal Studi Guru dan Pembelajaran, 2024)
The problem in this study concerns the lack of innovation by educators in the use of effective learning models and media to enhance the critical thinking abilities of learners. The aim of the research is to find out the effectiveness of brain-based learning by helping wordwall overcome the ability to think critically. Type of experimental research with pretest research design and posttest nonequivalent control group design. Data collection techniques using tests. A sample of 41 students was taken using saturated sampling. The data obtained was analyzed using the N-Gain test. The results of the analysis of the research data showed that brain-based learning with wordwall has an efficiency at a medium level of 0.3 ≤ g ≤ 0.7, with a N-Gain value of 0.47. This means brain-based learning supported by a wordwall can be applied in learning as well as effectively to improve the critical thinking ability of students.